AN INVESTIGATION OF FACTORS INFLUENCING TOURISTS’ LOYALTY TO REVISIT PHNOM PENH, CAMBODIA - Sophat, IM; Saroeun, Associate Prof. Dr. Tan; Hong, Assistant Prof. Dr. Soun (Srawung: Journal of Social Sciences and Humanities, 2024)
Phnom Penh, Cambodia’s capital is a popular destination for both domestic and foreign tourists because of its rich cultural legacy, numerous natural and man-made attractions, recreational facilities, retail possibilities, and tourist amenities. This research investigates factors influencing tourist loyalty in Phnom Penh, Cambodia, examining factors influencing tourists’ decisions and loyalty to Phnom Penh as a tourism destination reveals a high crime rate of 62.18% in 2018, with a 73.08% increase over the past of three years. Factors such as E-WOM, brand knowledge, and perceived risk contribute to this issue. Based on the literature, it has been determined that electronic word-of-mouth and destination brand knowledge are the independent variables, while destination brand knowledge is the dependent variable. This research uses a quantitative and correlational research methodology to gather data from 384 respondents using non-probability samplings. Further, the procedure of the statistical analytical tools is conducted using SPSS version 25 and the Analysis of Moment Structures (AMOS) version 23. As the statistical result, the study investigates the relationship between Electronic Word of Mouth (E-WOM), Destination Brand Knowledge, Perceived Risk, and Tourist Loyalty in Phnom Penh, Cambodia. It found a positive correlation between E-WOM and destination knowledge, influencing tourists’ decisions and loyalty. However, it also revealed a negative association between perceived risk and loyalty, suggesting strategies for risk mitigation and trust enhancement. The findings can help policymakers and stakeholders foster sustainable tourism growth and enhance destination competitiveness in Phnom Penh, Cambodia.